Yield performance for sorghum cultivars under thermal and saline stress in the Brazilian semi-arid region - Andrade, Mateus Ferreira; Siqueira, Tânia da Silva; França, José Geraldo Eugênio de; Simplício, Josimar Bento; Tabosa, José Nildo (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
This work aims to evaluate forage sorghum in the semi-arid region of Pernambuco, where salinity and water stress are present. The study was based on the premise that good management makes the soils arable and able to agricultural practices. Because it has an "aggressive" root system and a certain tolerance to salinity, sorghum can explore deeper layers of soil in search of water and nutrients and produce surprising yields. It also has protective cutin on the stalk and leaf surface, resulting in less water loss through transpiration. These factors allow it to better adapt to the adversities of this environment, such as temperatures above 40ºC, water and salt stress, and even so, it has shown satisfactory yields when compared to other Poaceae. This study aimed to evaluate 12 forage sorghum cultivars with different agronomic characteristics, under irrigation with water of up to 1.4 dS.m-1 from the Saco reservoir, during two successive cycles, characterizing the spring and summer seasons, in 2015 and 2016, respectively. The experiment was conducted in the experimental area of the IPA, Serra Talhada - PE. The design used was randomized blocks in a 2x12 factorial scheme, the first factor corresponding to two cropping systems (with and without mulch (C/C and S/C) and the second, 12 sorghum cultivars shown in Table 1. There were 22 treatments with 2 replications, totaling 44 experimental units. Each plot consisted of 3 rows 5 meters long, spaced 0.80m apart. The planting density after thinning was 15 plants per linear meter. At the end of the experiment, it was found that the cover cropping system (C/C) provided better yields of up to 30% in the 1st cycle and up to 64% in the 2nd cycle among the systems studied; the 2nd cycle was favored by rainfall which provided yields of up to 68.85 and 61.6 t.ha-1 MV and 24.10 and 21.56 t. ha-1 DM, respectively, in both the C/C and S/C cultivation conditions; the IPA SF 15 and BRS Ponta Negra varieties were responsible for the highest yields, with rates of over 120 and 100 t.ha-1 DM (C/C) and 86 and 90 t.ha-1 DM (S/C), respectively; in the 1st and 2nd cycles, the S/C cultivation system provided higher yields for the SF17, 2502 and SF190 varieties, respectively.